Peran Profitabilitas dalam Memediasi Nilai Perusahaan Sektor Makanan dan Minuman (The Role of Profitability in Mediating Value of Food and Beverage Companies) - Imron, Muhamad Ali; Putra, I Nyoman Nugraha Ardana (STIE Malangkucecwara, 2025)
This study aims to analyze the role of profitability as a mediating variable in the relationship between capital structure and dividend policy on firm value. To achieve these objectives, the population used in this study is the annual financial statements of food and beverage sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The sampling technique is purposive sampling. The data obtained were analyzed using Eviews 12 software, including model selection test, hypothesis testing, and Sobel test. The results show that capital structure, dividend policy, and profitability have no significant effect on firm value. In addition, profitability is negatively and significantly affected by capital structure and dividend policy, but cannot mediate the relationship between capital structure and dividend policy with firm value.